Moral Values: The Story of Asma' Bint Abu Bakar In Children Aged 5-6 Years - Alifah, Nyaknong Karti; Muthmainnah, Muthmainnah; Faisal, Muhammad (Journal of Islamic Education Students (JIES), 2024)
Children can learn noble moral values if they are introduced to them from an early age. However, based on initial observations, researchers found that children aged 5-6 years at the Dharma Wanita Kindergarten in East Bakongan, South Aceh, still lack good moral values. So this research aims to determine the influence of the story of Asma' bint Abu Bakar on the introduction of moral values in the school. This research uses an experimental method with a quantitative approach and uses a one group pre-test post test design. This study used 16 children aged 5-6 years, selected using total sampling techniques. Data were collected using research instruments in the form of observation sheets, then analyzed to determine normality tests and hypothesis tests. So the research results show the average pre-test score is 39.37% and the average post-test score is 78.75%. So it produces a normality test of 0.879 and a tcount>ttable test of 14.86>2.13145. This shows that Ha is accepted and Ho is rejected. So it can be concluded that the story of Asma' bint Abu Bakar has a significant influence on the introduction of children's moral values at the Dharma Wanita TK Bakongan Timur, South Aceh.